Axitinib in metastatic renal cell carcinoma: single center experience - Buraczewska, Agnieszka; Kardas, Joanna (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Due to the emergence of new therapeutic opportunities in the second-line treatment of metastatic renal cell carcinoma, the choice of the appropriate medication requires consideration. Making the selection one should take into account the likelihood of response, the probability of toxicity, properties of the drug and the clinical characteristics of the patient. Aim of the work was to confirm antitumor efficacy of axitinib in patients with metastatic clear-cell renal-cell carcinoma in the second line treatment remaining under the care of our institution. The primary objective was to determine antitumor activity, secondary – to evaluate progression free survival, safety of the treatment and to analyse clinical characteristics of treated population. Results: Treatment records of 27 patients (9 females, 18 males) treated from October 2014 to the present (July 2016) were reviewed. The median duration of treatment which corresponds to the time to disease progression in observed population was 6 months (range: under 1 month – 16 months). 1 patient (3.7%) had got objective response (PR, partial remission). Clinical benefit rate (PR + SD (stable disease) was 66%. 9 patients (33.33%) experienced treatment toxicity only in the first degree of CTCAE (common toxicity criteria for adverse events), 11 patients (40.74%) presented the second degree toxicity and 5 patients (18.5%) – third degree. The most commonly reported treatment related adverse events were diarrhea (47%), fatigue (26%), hand-foot syndrome (26%), deterioration of blood pressure control (22.2%), abnormal liver function tests (18.5%), mucositis (11.1%).We observed 3 cases of unacceptable toxicity. Conclusions : Axitinib confirms its effectiveness also in situ ation outside clinical trials, however, it is characterized by significant toxicity. Therefore, qualification for treatment should take into account the clinical patient characteristics. Effective diagnosis and treatment of side effects and dose optimization are the key skills of the attending physician.